A frameshift variant in the EDA gene in Dachshunds with X‐linked hypohidrotic ectodermal dysplasia. (2nd October 2018) - Hadji Rasouliha, S.; Bauer, A.; Dettwiler, M.; Welle, M. M.; Leeb, T.
Summary: X‐linked hypohidrotic ectodermal dysplasia (XLHED) is a genetic disease characterized by hypoplasia or absence of hair, teeth and sweat glands. The EDA gene, located on the X chromosome, encodes the type II transmembrane protein ectodysplasin A. Variants in the EDA gene can lead to XLHED in humans, mice, cattle and dogs. In the present study, we investigated a litter of Dachshund puppies, of which four male puppies showed clinical signs of XLHED. We performed a candidate gene analysis in one affected puppy and several non‐affected relatives. This analysis revealed a single base‐pair deletion in the coding sequence of the EDA gene in the affected puppy (NM_001014770.2 :c.842delT). The deletion is predicted to cause a frameshift, NP_001014770.1 :p.(Leu281HisfsTer22), leading to a premature stop codon which truncates more than one quarter of the EDA protein. Sanger sequencing results confirmed that this variant was inherited from the dam. Based on knowledge about the functional impact of EDA variants in dogs and other species, c.842delT is a convincing candidate causative variant for the observed XLHED in the male puppies.